Identification and description of the sociomotor sub-roles and the Ludogram of Brazilian jiu-jitsu - Schmidt, Vagner Augusto de Oliveira; Ribas, João Francisco Magno (Frontiers in Sports and Active Living, 2023)
Brazilian jiu-jitsu (BJJ) was conceived to be an oppositional sociomotor practice with an emphasis on self-defense, but throughout the 20th century, BJJ gained sporting features, modifying its internal logic (LI). In the case of BJJ, the richness of the motor itineraries can be revealed in the different sociomotor sub-roles. Considering the absence of research that identifies and describes the sub-roles and the Ludogram of BJJ, the following question was asked: how to systematize the Ludogram of sociomotor sub-roles of Brazilian jiu-jitsu in accordance with its internal logic? This work is characterized as a theoretical research that is dedicated to rebuilding theories and concepts, with a view, in immediate terms, to improving theoretical foundations. In this study, a theoretical reconstruction of the BJJ's operating dynamics was carried out, identifying roles and sub-roles, culminating in the construction of a Ludogram. The praxeological analysis was divided in two stages: 1) Description of the BJJ sub-roles based on sports rules and video analysis; 2) Systematization of the BJJ Ludogram. Eight videos of public and unrestricted access were selected, fights from the 2018 BJJ World Championship. The sample was considered based on the following criteria: convenience, typicality and saturation. The 26 identified and described sub-roles of BJJ indicate the richness of choices and possible paths to be followed by fighters within this itinerary of motor interaction. These different BJJ sub-roles described in this research highlighted the importance of the concept of praxis communication, specifically, motor counter-communication, since many of the dynamics between a fighter's sub-roles refer to the choices that the opponent indicates for the motor dialogue. BJJ will require from fighters incessant activations on aspects related to sociomotor intelligence, such as the need for sociomotor empathy, motor strategy, to anticipate anticipations, pre-acting, developing to motor decision, to recognize the affective, cognitive, relational and organic loads activated during the fight, to develop their motor conduct. In this sense, the Ludogram was elaborated, which enables future praxeological analyzes of the sub-roles and motor conducts of any subject who wants to assume the sociomotor role of a BJJ fighter, according to the rules of this Brazilian fight.